Integrating Physiology into the DNA of Coronary Revascularisation – A Historical Perspective, Contemporary Review and Blueprint for the Future of Coronary Physiology - Sayan, Sen (Interv Cardiol, 2015)
The clinical and economic benefits of physiologically guided revascularisation have been demonstrated, yet its clinical adoption remains unacceptably low. Recently, new indices of stenosis severity have been introduced that aim to improve adoption by circumventing the limitations of existing indices. The most validated of these new indices is the instantaneous wave-free ratio (iFR). This review will describe the physiological basis of this index, how it avoids the problems of existing indices such as fractional flow reserve (FFR) and the clinical validation studies of iFR to date. We will then describe a novel use of iFR, which has the potential to transform the use of physiology in the catheter lab and finally integrate physiology into the DNA of coronary revascularisation.